Формування iндивiдуального комплексу керувальних впливiв для реабiлiтацiї рухiв i мовлення пiсля iнсульту - Вовк, М.І.; Галян, Є.Б.; Куцяк, О.А.; Лаута, А.Д. (Кибернетика и вычислительная техника, 2018)
Розроблено загальний і додаткові алгоритми формування індивідуального комплексу керувальних впливів для реабілітації м’язових і мовленнєвих функцій після інсульту. Згідно з цими алгоритмами у пацієнта перевіряють наявність загальних і специфічних протипоказань до застосування міоелектростимуляції та/або біотренування, проводять кількісне оцінювання порушень рухових і мовленнєвих функцій, м'язового тонусу за новими оригінальними методиками, перевірку обмежень до застосування програм і тривалості тренувань. Разработаны общий и дополнительные алгоритмы формирования индивидуального комплекса управляющих воздействий для реабилитации двигательных и речевых функций после инсульта. Согласно алгоритмам у пациента проверяют наличие общих и специфических противопоказаний к применению миоэлектростимуляции и/или биотренировки, проводят количественную оценку нарушений двигательных и речевых функций, мышечного тонуса по новым оригинальным методикам, проверку ограничений к применению программ и продолжительности тренировок. Разработаны решающие правила с применением алгебры предикатов и логических переменных, которые соответствуют указанным критериям и показателям. Согласно этим правилам в бинарной форме на каждом этапе реабилитации определяют рекомендуемые по приоритету наборы движений и программ тренировок ("Синтез", "Донор", "Порог", "Биотренировка" по технологии ТРЕНАР®) и их регламент. A general and additional algorithms for the formation of an individual complex of control actions for motor and speech functions rehabilitation after a stroke have been developed. According to the algorithms, the patient is tested for general and specific contraindications to the use of muscle electrical stimulation and / or biofeedback training, quantitative assessment of motor and speech functions, muscle tonus according to new original techniques, verification of limitations to the application of programs and the duration of training. Additional algorithms are designed taking into account both hyper- and hypotonic parameters. A special feature of these algorithms is the introduction of additional restrictions, for which intervals of muscle tone values are formed. Decision rules have been developed using the algebra of predicates, logical variables corresponding to the specified criteria and indicators. According to these rules, in each stage of rehabilitation, a set of movements and training programs recommended by priority ("Synthesis", "Donor", "Threshold", "Biofeedback" according to TRENAR® technology) and their schedule are determined in binary form.